Delivery Room Intensive Care Unit: 5 Years' Experience in Assistance of High-Risk Newborns at a Referral Center - Buratti, Silvia; Lampugnani, Elisabetta; Faggiolo, Monica; Buffoni, Isabella; Paladini, Dario; De Tonetti, Gabriele; Tuo, Giulia; Marasini, Maurizio; Mattioli, Girolamo; Moscatelli, Andrea (Frontiers in Pediatrics, 2021)
To describe a Delivery Room Intensive Care Unit (DRICU) model and evaluate its effectiveness in preventing morbidity and mortality in high-risk newborns. Retrospective case series of all DRICU procedures performed from 2016 to 2020. Gaslini Children’s Hospital is a major pediatric tertiary care center where high-risk pregnancies are centralized. The Neonatal and Pediatric Intensive Care Unit admits every year about 100 high-risk newborns. Newborns at risk of critical conditions immediately after birth for respiratory or cardiovascular congenital disorders. The perinatal plan is defined by the multidisciplinary team of Fetal and Perinatal Medicine. The DRICU procedure provides highly specialized care through a protocol that includes logistics, personnel, equipment, and clinical pathways. The primary outcome is the prevention of acute complications and mortality in the delivery room and early neonatal period. From 2016 to 2020 40 DRICU procedures were performed. Main prenatal diagnoses included: congenital heart disease with a high risk of life-threatening events immediately after birth (38%), congenital diaphragmatic hernia (35%), and fetal hydrops/hydrothorax (23%). Mean gestational age was 35.9 weeks (range: 31-39), mean birth weight was 2740 grams (range: 1480-3920). DRICU assistance completed in all patients by neonatal intensivists included tracheal intubation and arterial and central venous cannulation; complex procedures such as ex-utero intrapartum technique and ECMO cannulation are described. No deaths nor severe acute complications occurred in the delivery room or in the immediate postnatal period. The outcome in critical newborns is potentially affected by planned assistance strategies and specialized competencies through the implementation of a DRICU protocol.